New Technology and Competition in the Information Space of Kazakhstan. (Herald of Journalism, 2016)
The paper discusses the information field of the Kazakhstan in competition with foreign Media, the formation of Impact news, by creating Information Cards among on-line resources and a place of the foreign information. The author reveals the mechanism of formation of the Information landscape, which affects the political, economic and social position of the country, the information security of the state. The author used the methodology of typological analysis to support the analytical position, allowing to identify the emergence of a « bad» and «good» news in the information field in Kazakhstan.
Keywords: information security; competition news; online resources; «bad» and «good» news; Kazakhstan